From early adversities to immune activation in psychiatric disorders: the role of the sympathetic nervous system. (14th August 2019) - Mondelli, V.; Vernon, A. C.
Summary: Increased peripheral levels of cytokines and central microglial activation have been reported in patients with psychiatric disorders. The degree of both innate and adaptive immune activation is also associated with worse clinical outcomes and poor treatment response in these patients. Understanding the possible causes and mechanisms leading to this immune activation is therefore an important and necessary step for the development of novel and more effective treatment strategies for these patients. In this work, we review the evidence of literature pointing to childhood trauma as one of the main causes behind the increased immune activation in patients with psychiatric disorders. We then discuss the potential mechanisms linking the experience of early life adversity (ELA) to innate immune activation. Specifically, we focus on the innervation of the bone marrow from sympathetic nervous system (SNS) as a new and emerging mechanism that has the potential to bridge the observed increases in both central and peripheral inflammatory markers in patients exposed to ELA. Experimental studies in laboratory rodents suggest that SNS activation following early life stress exposure causes a shift in the profile of innate immune cells, with an increase in proinflammatory monocytes. In turn, these cells traffic to the brain and influence neural circuitry, which manifests as increased anxiety and other relevant behavioural phenotypes. To date, however, very few studies have been conducted to explore this candidate mechanism in humans. Future research is also needed to clarify whether these pathways could be partially reversible to improve prevention and treatment strategies in the future. Abstract :